2015
DOI: 10.1152/ajpgi.00095.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of proteins involved in energy production along the crypt-villus axis in early-weaning pig small intestine

Abstract: Weaning of piglets reflects intestinal dysfunction and atrophy and affected the physiological state of enterocytes. However, few studies have defined physiological state of enterocytes along the crypt-villus axis in early-weaning piglets. A total of 16 piglets from 8 litters were used in the experiment. One group of piglets was nursed by sows until age 21 days, and another group was weaned at age 14 days and then fed creep feed instead of breast milk for 7 days. Piglets were killed at 21 days, and the jejunum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 40 publications
5
44
0
3
Order By: Relevance
“…In the current study, Cu supplementation increased villus height, which was in agreement with Shurson et al (1990) and in contrast to previous studies reporting no effect of high Cu supplementation on villus height (Radecki et al 1992;Hedemann et al 2006). It is well known that in piglets villus atrophy and crypt hyperplasia occur after weaning (Xiong et al 2015). The earlier the weaning, the more prominent these morphological changes.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, Cu supplementation increased villus height, which was in agreement with Shurson et al (1990) and in contrast to previous studies reporting no effect of high Cu supplementation on villus height (Radecki et al 1992;Hedemann et al 2006). It is well known that in piglets villus atrophy and crypt hyperplasia occur after weaning (Xiong et al 2015). The earlier the weaning, the more prominent these morphological changes.…”
Section: Discussionsupporting
confidence: 89%
“…In the mature intestine, where rapid growth in intestinal crypts feeds differentiated cells onto the villi, it was recently observed that the proliferating progenitor cells exhibit a more glycolytic metabolism than their differentiated counterparts (Stringari et al, 2012;Xiong et al, 2015). A key role of future studies will be to determine whether metabolic states are dependent on developmental signaling processes, whether developmental signaling processes depend upon metabolic states, or most likely an interdependence of the two processes.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial cells were isolated using the distended intestinal sac method as previously described with slight modifications [11,12]. The divided mid-jejunum segments were rinsed thoroughly with ice-cold physiological saline solution and incubated at 37°C for 30 min with oxygenated PBS.…”
Section: Sequential Isolation Of Epithelial Cells Along Cvamentioning
confidence: 99%
“…The isolated cells were immediately frozen in liquid nitrogen and then stored at -80°C until analysis. The efficiency of fractionation cell was validated by measuring alkaline phosphatase and PCNA as previously described [12]. The activity of alkaline phosphatase was determined using an enzyme assay kit, according to the manufacturer's protocol (Nanjing Jiancheng Bioengineering Institute, Nanjing, China) [13].…”
Section: Sequential Isolation Of Epithelial Cells Along Cvamentioning
confidence: 99%